2021
DOI: 10.1097/aog.0000000000004627
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Complications in Women With Congenital Uterine Anomalies According to the 2013 European Society of Human Reproduction and Embryology and the European Society for Gynaecological Endoscopy Classification

Abstract: To assess the risk for obstetric complications in women with congenital uterine anomalies and the risk in each main class of uterine anomaly (U2 [septate], U3 [bicorporeal], U4 [hemi-uterus]), based on the 2013 classification by the ESHRE (European Society of Human Reproduction and Embryology) and the ESGE (European Society for Gynaecological Endoscopy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
2
15
0
1
Order By: Relevance
“…The incidence of uterine anomalies is suspected to be 3%–5% among infertile women, and a septate uterus is known to have higher risks of early spontaneous abortions or obstetrical complications. 20 , 21 Even an arcuate uterus is associated with an increased risk of preterm birth and fetal growth restriction. 22 Several studies have shown elevated incidences of uterine anomalies in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of uterine anomalies is suspected to be 3%–5% among infertile women, and a septate uterus is known to have higher risks of early spontaneous abortions or obstetrical complications. 20 , 21 Even an arcuate uterus is associated with an increased risk of preterm birth and fetal growth restriction. 22 Several studies have shown elevated incidences of uterine anomalies in women with PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of repeat dystocia is low (around 10%). However, additional risk factors such as increased fetal weight and diabetes in the current pregnancy may lead toward cesarean delivery. ‐ Plan cesarean : >4500 g fetus—diabetics : estimated risk of shoulder dystocia >15% 17 Mechanical obstacle to vaginal birth (macrocephaly) 21 ‐ Offer vaginal birth : Fetal ventriculomegaly, but normal head circumference measured, and in the absence of other obstetric indications. ‐ Plan cesarean delivery : Fetal macrocephaly, only when the head circumference is >40 cm, large head 19 …”
Section: Indications For Cesarean Delivery and Vaginal Delivery When ...mentioning
confidence: 99%
“…The risk of repeat dystocia is low (around 10%). However, additional risk factors such as increased fetal weight and diabetes in the current pregnancy may lead toward cesarean delivery. ‐ Plan cesarean : >4500 g fetus—diabetics : estimated risk of shoulder dystocia >15% 17 …”
Section: Indications For Cesarean Delivery and Vaginal Delivery When ...mentioning
confidence: 99%
“…There are no reliable diagnostic tests or markers to predict or prevent the occurrence of placental abruption. Its risk factors include advanced maternal age, multiparity, smoking, cocaine and drug use, pre-eclampsia, chronic hypertension, premature rupture of membranes, trauma, polyhydramnios, structural uterine anomalies, and a history of placental abruption [7][8][9][10] . This study aims to identify risk factors for placental abruption and evaluate maternal and fetal outcomes of patients with placental abruption in a tertiary hospital in Hong Kong.…”
Section: Introductionmentioning
confidence: 99%